Գրիգոր Լուսավորչի ագաթանգեղոսությունից մինչև «Ագաթանգեղայ Պատմութիւն Հայոց» - Ա. Ս. Սահակյան (ՀՀ ԳԱԱ հրատ.)
В 80-х гг. III в. Григорий Парфянин как странствующий проповедник христианства в Каппадокии, Малой и Великой Армении получил прозвище Агафангел. После провозглашения христианства в качестве государственной религии царем Тиридатом Великим, начиная с середины века на основе связанных с именем Григория Агафангела чудодеяний в рамках монастырского фольклора стал формироваться устный роман об обращении армян в христианство, названный "История Агафангела" или " Повесть об Агафангеле". In the 80s of the 3rd century, being an evangelist in Cappadocia, Lesser and Greater Armenias, Gregory Parthev was named Agathangelos. After Trdat the Great made Christianity the state religion in Armenia, in the middle of the 4th century a tale about the magical deeds of Gregory Agathangelos was formed within the circles of Armenian monastic folklore that was called “History of Agathangelos” or “The Story of Agathangelos”.
Keywords: History; B Philosophy; Psychology; Religion; Geography; Anthropology; Recreation; Medieval History; Folklore; BR Christianity; D History